La perdita del sacro timore - Tamaro, Susanna (Firenze Architettura, 2022)
La natura ci parla della bellezza, di un mondo che esiste e vive sotto il segno della complessità. Ma sebbene la natura sia diventata un totem ideologico davanti al quale immolare le nostre ansie e paure più profonde, è assente l’idea che il degrado ambientale sia in qualche modo legato al degrado della nostra anima. Nature speaks to us of beauty, of a world that exists and lives under the sign of complexity. And although nature has become an ideological totem before which we can offer as sacrifice our deepest anxieties and fears, the idea that environmental degradation is in some way related to the degradation of our soul is lacking.